Respostas
respondido por:
1
a= -1
b=0
c=4
∆=0²- 4.(-1).4
∆=0 + 16
∆= 16
x= 0+-√16/2.(-1)
x1= +4/-2= -2
x2= -4/-2= +2
ou nesse caso se preferir pode fazer assim também pois não tem o termo de b
-x²+4=0
-x²= - 4
x²=4
x=+-√4
x1= -2 e x2= +2
b=0
c=4
∆=0²- 4.(-1).4
∆=0 + 16
∆= 16
x= 0+-√16/2.(-1)
x1= +4/-2= -2
x2= -4/-2= +2
ou nesse caso se preferir pode fazer assim também pois não tem o termo de b
-x²+4=0
-x²= - 4
x²=4
x=+-√4
x1= -2 e x2= +2
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás